Unlocking the potential of trace cobalt in Ni-based superalloys: A molecular dynamics study on dislocation behavior and high-temperature stability - Huicong Dong; Yinghao Chen; Dayong Wu; Haikun Ma; Zhihao Feng; Ru Su (Materials & Design)
Cobalt (Co) is one of the fastest diffusing elements in Nickel (Ni)-based single crystal superalloys, playing a critical role in stabilizing the γ matrix and γ′ precipitate, and influencing dislocation behavior and deformation mechanisms. Existing studies focused on high Co content effects, however, the potential mechanisms of trace Co additions may differ significantly from those of high Co content due to their localized atomic interactions. These differences, particularly influence of trace Co on dislocation evolutions, remain underexplored, lacking detailed atomistic insights. Here, we investigated mechanical responses to trace Co additions and variations temperatures, alongside dislocation evolution during uniaxial tension tests. Results show that the 0.25% Co alloy consistently exhibits higher strength than the principle alloy across the temperature range. At this composition, dislocation loops create a drag effect, hindering dislocation slip into γ′ precipitate. A “Cottrell atmosphere”-like pinning effect unique to 0.25 vol% Co further prevents dislocation penetration into γ′. As temperature increases, the dominant deformation mechanism transitions from dislocation shear to dislocation climb. Notably, the 0.1 vol% Co alloy shows persistent dislocation tangles, resulting in the highest yield strength at elevated temperatures. These findings offer valuable insights for optimizing the composition and microstructural design of Ni-based single crystal superalloys.